Imagining Alternative Spaces: Re-searching Sexualized Violence with Indigenous Girls in Canada. Issue 3 (1st December 2019) - Chadwick, Anna
Abstract : "Sisters Rising" is an Indigenous-led, community-based research study focused on Indigenous teachings related to sovereignty and gender wellbeing. In this article, I reflect on the outcomes of re-searching sexualized violence with Indigenous girls involved with "Sisters Rising" in remote communities in northern British Columbia, Canada. Through an emergent methodology that draws from Indigenous and borderland feminisms to conduct arts- and land-based workshops with girls and community members, I seek to unsettle my relationships to the communities with which I work, and the land on which I work. I look to arts-based methods and witnessing to disrupt traditional hegemonic discourses of settler colonialism. I reflect on how (re)storying spaces requires witnessing that incorporates (self-)critical engagement that destabilizes certainty. This position is a critical space in which to unsettle conceptual and physical geographies and envision alternative spaces where Indigenous girls are seen and heard with dignity and respect.